2012
DOI: 10.1007/s00277-012-1405-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hepatitis B surface antibody titers in B cell lymphoma patients after rituximab therapy

Abstract: Hepatitis B virus (HBV) reactivation is a well-known complication after rituximab therapy in patients with B cell lymphoma. Traditionally, hepatitis B surface antibody (anti-HBs) is a protective antibody, but the effect of rituximab on these antibodies has not been well studied. In 29 B cell lymphoma patients who were positive for anti-HBs before rituximab therapy, anti-HBs serologies before and after rituximab therapy were compared. Anti-HBs titers after rituximab treatment were significantly lower (P < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 24 publications
6
74
3
2
Order By: Relevance
“…Although these cases are not completely accurate since we cannot measure titers above 1000 mIU/mL, in these patients, the titers probably did not drop below 1000 mIU/mL. Pei et al [57] reported anti-HBs antibody titers after rituximab therapy and concluded that the risks of HBV reactivation are the reduction of anti-HBs titers, especially low pretreatment anti-HBs titers and the loss of anti-HBs. These results on titer changes might provide an index for preventive lamivudine or entecavir administration in patients who are only anti-HBs-positive.…”
Section: Anti-hbc-positive Anti-hbs-negative and Hbsagnegative Casesmentioning
confidence: 86%
“…Although these cases are not completely accurate since we cannot measure titers above 1000 mIU/mL, in these patients, the titers probably did not drop below 1000 mIU/mL. Pei et al [57] reported anti-HBs antibody titers after rituximab therapy and concluded that the risks of HBV reactivation are the reduction of anti-HBs titers, especially low pretreatment anti-HBs titers and the loss of anti-HBs. These results on titer changes might provide an index for preventive lamivudine or entecavir administration in patients who are only anti-HBs-positive.…”
Section: Anti-hbc-positive Anti-hbs-negative and Hbsagnegative Casesmentioning
confidence: 86%
“…5C). Recently, it was reported that the reduction or the loss of anti-HBs antibody during or after the treatment was followed by HBV reactivation (42,43). Therefore, the ICT-CLEIA assay, which is able to detect HBsAg before the loss of anti-HBs antibody, might be useful for the earlier diagnosis of HBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Pei et al reported that 8 of 10 (80%) HBsAg-positive patients developed HBV reactivation in a retrospective analysis. 26 More recently, Kim et al conducted a multinational retrospective study to evaluate the incidence of HBV reactivation and its risk factors and found that 13 of 22 (59%) HBsAg-positive patients had HBV reactivation without antiviral prophylaxis. 24 …”
Section: Risk Of Hbv Reactivation After Immunosuppressive Therapymentioning
confidence: 99%
“…7,28,29 The incidence of HBV reactivation in HBsAg-positive patients receiving rituximabcontaining chemotherapy without antiviral prophylaxis has been reported to be 59%-80%. 24,26 These patients are considered to constitute a very-high-risk group for HBV reactivation (Figure 1). Of the HBsAg-positive patients, most HBV reactivation occurs during and after chemotherapy, but patients with high HBV DNA levels at baseline potentially suffer HBV reactivation at an early stage of chemotherapy.…”
Section: Strategy To Prevent Hbv Reactivation In Hbsag-positive Patientsmentioning
confidence: 99%